Appropriateness of written dosing instructions provlded with dispensed medicines by pharmacists - A hospital and community experience - Manchanayake, M.G.C.A.; Bandara, G.R.W.S.K.; Samaranayake, N.R. (Pharmaceutical Journal of Sri Lanka 2016, 2016)
Attached